Morphological Structures in Korean and their Implications for Language Typology - Saydazimova, Umida; Jung, Park Mi; Young, Jo Min; Murodova, Durdona; Khidoyatova, Aziza; Abdullaeva, Feruza (Indian Journal of Information Sources and Services, 2025)
The paper discussed the Korean morphosyntactic structures within the context of linguistic typology. It analyzes the morphological system of Korean agglutination, honorifics, and discourse-sensitive markers in light of classical and contemporary models of linguistic classification. As much as Korean tends to conform to agglutinative typology, it is also marked by morphophonological fusion, pragmatic ellipsis, and zero anaphora, which blur the lines of categorization. The paper represents Korean as a bridge language that straddles a hybrid typological terrain while illustrating the problem posed by morphosyntactic fusion shared between Trans Eurasian and non-agglutinative languages. From a comprehensive perspective, incorporating disparate descriptions and theories, the study argues for the role of usage-based multidimensional models of typology. It enhances the understanding of the interplay between morphology, discourse, and grammar.